Relationships among retinal/choroidal thickness, retinal microvascular network and visual field in high myopia - Wu, Qiuyan; Chen, Qi; Lin, Bing; Huang, Shenghai; Wang, Yuanyuan; Zhang, Lingmin; Lin, Huiling; Wang, Jianhua; Lu, Fan; Shen, Meixiao (Acta ophthalmologica (Oxford, England), 2020)
Purpose To determine the relationships among retinal/choroidal thickness, retinal microvascular network and visual field in high myopia. Methods This cross‐sectional study included a total of 62 subjects, comprising 31 eyes with high myopia and 31 eyes with emmetropia or low myopia. Optical coherence tomography was used to quantify the thickness of ganglion cell complex (GCC), inner nuclear layer and outer plexiform layer (INOPL), outer retinal layer (ORL) and choroid layer (ChL). Optical coherence tomography angiography was used to quantify the superficial vessel density (SVD) and deep vessel density (DVD). Retinal light sensitivity (RLS) was measured by microperimetry‐1 (MP1). The inner ring (1–1.75 mm), the outer ring (1.75–2.5 mm) and the whole ring (1–2.5 mm) around the macula were analysed and compared between the two groups. Pearson correlation analysis was performed to analyse the relationship among them. Results In the highly myopic group, the thinning of retinal/choroidal thickness and the decrease in retinal vessel density and RLS were found when compared to the emmetropia or low myopia (p < 0.05). Decreased RLS was correlated with decreased ORL thickness (r = −0.469, p = 0.008) and choroid thickness (r = 0.398, p = 0.030). There was no correlation between retinal microvascular network parameters and RLS (p > 0.05), but DVD showed a negative correlation with ORL (r = −0.474, p = 0.007). Conclusion Early visual field defects in highly myopic eyes may be influenced by the ORL loss and defect of choroidal circulation. The deep retinal microvascular network may have a compensatory action in the hypoxic setting of high myopia.